AB0699 Enthesitis and Sacroiliitis Prevalence Determined by Doppler Ultrasonography and Magnetic Resonance Imaging in Patients with Inflammatory Bowel Disease. (15th July 2016) - Aparicio, M.; Ruiz-Cerulla, A.; Narváez, J.A.; Moragues, C.; Peñalva, M.; Michelena, X.; Nolla, J.M.; Guardiola, J.; Juanola, X.
Abstract : Background: Patients with inflammatory bowel disease (IBD): Crohn disease (CD) and ulcerative colitis (UC) can develop extraintestinal manifestations and ones of the most important are musculoskeletal affections. In published studies, the prevalence of Spondyloarthritis (SpA) stands from 10 to 20% but with a wide range of variation. These differences are related to the methods used for its determination. Objectives: 1) To determine the prevalence of sacroiliitis with X-ray or magnetic resonance imaging (MRI) and of enthesitis with Doppler ultrasonography in patients with active IBD without following an immunosuppressant therapy 2) To check the prevalence of patients with positive ASAS criteria for axial and peripheric SpA. Methods: Cross-sectional study in which a sample of patients diagnosed of active IBD, without previous diagnosis of rheumatic inflammatory disease and without any previous immunosuppressant therapy, underwent a comprehensive rheumatologic examination addressed to detect musculoskeletal SpA features. Data collected comprised: demographics, family medical history, IBD characteristics and comorbidities, axial symptoms, swollen and tender joint counts (44/46 joints), entheses and dactylitis examinations, BASDAI and BASFI questionnaires and CRP and HLAB27 blood tests. The following image techniques were also applied: cervical, lumbar column and pelvis X-ray, sacroiliac MRI with T1 and STIR sequence and ultra-sound exploration of entheses. Results: 30 patients (16 women) with a mean age 39.8 (9, 8) years have been studied. 16 had CD and 14 UC. 16% tested positive for B27. 14 patients referred chronic lumbar pain, 4 of them with inflammatory characteristics. 10 patients referred arthralgias, without joint swelling o redness and 3 patients had history of heel pain, although they were not explored for any physician. None of the patients did not refer past medical history of uveitis or psoriasis (family or own history). 36% of the patients had MRI signs of sacroiliac inflammation that met ASAS criteria. One of the patients had grade 3 radiographic sacroiliitis and one patient with inflammatory signs in sacroiliac joints by MRI did not refer chronic lumbar pain. Ultrasound alterations were found in at least one enthesis within 97% of the patients: entheses calcifications (72%), bursitis (61%) and erosion (5%). Conclusions: In patients with active IBD not previously diagnosed with SpA, the existence of sacroiliitis and ultrasound alterations in entheses is frequent (36% and 97%, respectively). The prevalence of patients meeting axial SpA ASAS criteria is 32% and for peripheral criteria is 10%. The lower frequency of peripheral SpA can be attributed to an earlier diagnose of this form of presentation or to a lack of sensitivity of the peripheral SpA ASAS criteria on patients with IBD. Addition of ultrasound results in classification criteria could take into account patients with enthesitic signs earlier. Disclosure of Interest: None declared